Modifiers of Response to Treatment With Fesoterodine for Urgency-Predominant Urinary Incontinence in a Randomized Controlled Trial. Issue 2 (March 2017) - Winkelman, William D.; Huang, Alison J.; Schembri, Michael; Rogers, Rebecca G.; Richter, Holly; Myers, Deborah L.; Kraus, Stephen R.; Johnson, Karen C.; Hess, Rachel; Gregory, Tomas; Bradley, Catherine S.; Arya, Lily; et al.
Abstract : Objective: The aim of this study was to identify clinical and demographic characteristics that moderate response to treatment with fesoterodine among women with a diagnosis of urgency-predominant urinary incontinence. Methods: A multicenter, double-blinded, 12-week randomized controlled trial of pharmacologic therapy for urgency-predominant urinary incontinence in community-dwelling women diagnosed by the 3-item Incontinence Questionnaire (3IQ) was previously performed. Participants (N = 645) were randomized to fesoterodine therapy (4–8 mg daily; n = 322) or placebo (n = 323). Urinary incontinence was assessed by 3-day voiding diaries. In this secondary analysis, a "responder" was defined as reduction of 50% or greater in overall incontinence episode frequency compared with baseline. Clinical and demographic characteristics that may moderate treatment response were assessed by testing for interaction between characteristics and intervention in logit models of responders, adjusting for clinical site. Results: Participants' ages were a mean of 56 (SD, 14) years, 68% were white race, and they had a mean of 3.9 (SD, 3.0) urgency incontinence episodes per day. There were no baseline differences in demographic, clinical, or incontinence characteristics between treatment and placebo groups or between responders and nonresponders. There was an increase in the proportion of responders to fesoterodine with increasing age ( P = 0.04) and parity (0.04) and among married women ( P = 0.03), but no effect modification was observed by race/ethnicity, body mass index, education, employment status, or alcohol or tobacco use. Conclusions: In ambulatory women with urgency-predominant urinary incontinence, older age, being married, and higher parity significantly moderated and potentiated the effects of pharmacologic therapy on incontinence frequency. This study identifies certain populations who may have increased responsiveness to treatment with antimuscarinic therapy and may be used to inform and guide future therapy. Abstract : In a randomized controlled trial of participants with urge-predominant urinary incontinence, older age, being married and higher parity significantly moderated and potentiated the effects of pharmacological therapy on incontinence frequency.